Simulation of spatial variation of plankton communities in the South Central Vietnam sea by ROMS model - Vui, Vu Thi (Vietnam Journal of Marine Science and Technology, 2019)
This study preliminarily applies the Regional Ocean Modeling System (ROMS) in the two major monsoon seasons (Northeast and Southwest monsoons) for the South Central Vietnam sea (9–14.5oN, 105–112oE), in which the hydrodynamic and ecological modules are coupled. The results show that the plankton only develop in 200 m water on the top, concentrated mainly in the 0–70 m layer and in maximum biomass of 15–40 m layer. In the Northeast monsoon season, the plankton are concentrated mainly in the northern part and open seas of the area, while in the Southwest monsoon season, they are concentrated in the upwelling and adjacent southern areas. These results correctly reflect the basic law of the development of plankton communities in the sea area.